Komik Literasi Berbasis Kearifan Lokal: Media Pengembangan Karakter dalam Membangun Profil Pelajar Pancasila pada Anak Usia Dini: Literacy Comics Based on Local Wisdom: Character Development Media in Building Pancasila Student Profiles in Early Childhood - Ni'mah, Roudlotun; Ahmad Farid Utsman (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2024)
The aim of this research is to develop literacy comic learning media based on local wisdom of Tuban culture for group B children at RA Mambaul Islam in order to instill children's character values to build a Pancasila student profile. The type of method used by researchers is R&D (Research and Development) with the ADDIE development model. The validity test was assessed based on media experts, material experts, language experts, RA Mambaul Islam teachers, and 15 parents of group B RA Mambaul Islam students. The results of the percentage of media experts were 85% in the valid category, the percentage of material experts was 91% in the very valid category, and the percentage of language experts was 76% in the valid category. The test results for RA Mambaul Islam teachers were 88% with a very valid category and 15 parents of group B RA Mambaul Islam students had a percentage of 90% with a very valid category. From these results, it can be concluded that literacy comics based on local wisdom of Tuban culture in education instilling children's character values to build Pancasila student profiles in early childhood are valid and suitable for use in children's learning at RA Mambaul Islam.   ABSTRAK Tujuan dari penelitian ini adalah untuk mengembangkan media pembelajaran komik literasi berbasis kearifan lokal budaya tuban untuk anak kelompok B di RA Mambaul Islam  guna menanamkan nilai karakter anak untuk membangun profil pelajar Pancasila. Jenis metode yang digunakan peneliti adalah R&D (Research and Development) dengan model pengembangan ADDIE. Uji validitas dinilai berdasarkan dari ahli media, ahli materi, ahli bahasa, guru RA Mambaul Islam, dan 15 orang tua siswa kelompok B RA Mambaul Islam. Hasil presentase ahli media sebesar 85% dengan kategori valid, presentase ahli materi sebesar 91% dengan kategori sangat valid, dan presentase ahli bahasa sebesar 76% dengan kategori valid. Hasil uji coba terhadapat guru RA Mambaul Islam sebesar 88% dengan kategori sangat valid dan 15 orang tua siswa kelompok B RA Mambaul Islam sebesar presentase 90% dengan kategori sangat valid. Dari hasil tersebut, maka dapat disimpulkan bahwa komik literasi berbasis kearifan lokal budaya tuban dalam edukasi menanamkan nilai karakter anak untuk membangun profil pelajar Pancasila pada anak usia dini valid dan layak digunakan dalam pembelajaran anak di RA Mambaul Islam.